GENTETIC VARIABILITY, CORRELATION AND DIVERSITY STUDIES IN BREAD WHEAT (Triticum aestivum L.) GERMPLASM - Kalimullah; S. J. Khan; M. Irfaq; H. U. Rahman (Journal of Animal and Plant Sciences, 2012)
Forty one bread wheat genotypes grown in Peshawar, Pakistan during winter 2009-2010 were evaluated for variability parameters and correlation for number of grains/spike, number of tillers per plant, 1000-grain weight, flag leaf area, grain yield per plant and spike density. Significant genotypic differences were observed for all the traits studied indicating considerable amount of variation among genotypes for each character. The estimates of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were high for grain yield per plant, flag leaf area and number of tillers per plant. The remaining traits exhibit moderate to low PCV and GCV estimates. High heritability estimates were recorded for all the traits studied. These traits also indicate high expected genetic advance except spike density and number of tillers per plant. Grain yield per plant showed highly significant positive correlation with number of tillers per plant and number of grains/spike and significant positive correlation with 1000-grain weight. Based on Euclidian dissimilarity distance, the cluster analysis separated the 41 wheat genotypes into eight different clusters.
Keywords: Genetic variability; bread wheat germplasm; correlation.